The Influence of Working Capital and Inventory Turnover on Profitability in Auto Components Companies Listed - Muharani Fiannisa; Aji Prabowo (Journal of Management and Business Analytics, 2025)
This study was studied to determine the effect of Working Capital and Inventory Turnover on Profitability in Auto Components Sub-Sector Companies  listed on the Indonesia Stock Exchange in 2023-2024. The sampling method in this study uses the purposive sampling  technique so that the number of samples selected is 12 companies. The data analysis method used in this study is multiple linear regression analysis using an analysis tool, namely SPSS 26. Based on the results of the partial test, working capital has a calculated t  value of 2.893 > t table 2.035 and a significance level of 0.007 < 0.05 which means that  working capital has an effect on profitability. The results of the partial test of inventory turnover have  a calculated t  value of 0.606 < t table of 2.035 and a significance level of 0.548 > 0.05 which means that inventory turnover has no effect on profitability. Meanwhile, the results of the simultaneous test of working capital and inventory turnover have a calculated f  value of 4.325 > f table 3.28 and a significance level of 0.021 < 0.05 which means that working capital and inventory turnover have an effect on profitability in Auto Components sub-sector companies  listed on the Indonesia Stock Exchange in 2023-2024. The determination coefficient that can be seen from the Adjusted R-Square  value of 0.160, this can be interpreted as the ability of Working Capital and Inventory Turnover to affect Profitability of 16.0%.